The Utilization of Fiction Movies in Teaching Writing Skill - Achmad Jelalus Suyuti (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2022)
Writing is an essential element for the students in the modern era. Through writing, students can express and share their ideas, thoughts, experiences, and knowledge with others through a written form. However, teaching writing may be a challenge for the teachers, since writing is treated as a difficult skill in English learning. One of mediums that can be used in teaching writing using fiction movies. Fiction movies is a work of visual art used to simulate experiences that communicate ideas and stories. This study aims to describe the implementation and students' responses to the use of fiction movies in teaching writing. The research design of this research is qualitative which focuses on case study research. This research involved basic class students in the Excellent course Bangkalan as research subjects. Data were obtained through observation during the teaching and learning process and interviews with students. In this study, the researcher took several steps to analyze the data, namely organizing and familiarizing, coding and reducing, interpreting and representing. The findings of the first study revealed that Fiction movies were used by teachers and students both inside and outside the classroom. The teacher uses this media to facilitate writing techniques with 3 action resistance. The second finding revealed that students gave positive responses to the use of fiction movies in writing. The students said that Fiction movies is a media that is user-friendly, effective, and interesting and makes it easier to write structured. In addition, it also develops students' writing skills, and is able to motivate students in writing.